STUDY OF THE ECOLOGICAL RESTORATION OF AQUATIC MACROPHYTES IN A EUTROPHIC SHALLOW LAKE - 邱东茹 吴振斌 严国安 李益健 周远捷 (Chinese journal of oceanology and limnology, 1997)
Investigations in 1991 to 1993 showed that a perennial submerged plant,Potamogeton maackianus A. Benn, which always dominates the submerged vegetation in the shallow lakes in the middle and lower basins of the Changjiang River, had been extinct from Donghu Lake of Wuhan, and that some other submerged plants sensitive to water contamination had also dissappeared or declined in the lake. The r-selected species,Najas marina L.,Myriophyllum spicatum L. andVallisneria sp. had superseded the K-selected one,P. maackianus, to co-dominate the submerged vegetation. Several hypereutrophic or eutrophic subregions had switched from macrophyte dominance to phytoplankton dominance, while the shrinkage of macrophytes and the deterioration of water quality had also become more and more severe in the other subregions. The emergent macrophytes were poorly developed and the share of leaf-floating plants had increased in the lake. It was found that the existing vegetation fluctuated drastically from year to year. Macrophyte restoration experiments carried out in large enclosures at 3 subregions of different trophic state, suggested that the aquatic vegetation of less polluted sublakes, such as Niuchao, Tanglin and Houhu Lakes, could recover spontaneously after stocking of herbivorous fish stopped; that K-selected plants should be introduced into these sublakes to enhance the stability of aquatic vegetation; that a prerequisite for the recovery of macrophytes in the severely polluted basins is the reduction of external and internal nutrient loadings coupled with feasible management measures; and that r-selected submerged species should be used as pioneer plants for the macrophyte recovery. The recently introduced exotic submerged plant,Elodea canadensis, transplanted into the Houhu Enclosure could survive but failed to survive summer in the enclosures located in the hypereutrophic Shuiguohu Bay.[PUBLICATION ABSTRACT]